Bonn call for action and the unfinished task of radiation protection of children and adolescents in low and middle-income countries: A focus on Sub-Saharan Africa. Issue 3 (August 2021) - Nkubli, F.B.; Joseph, D.Z.; Yao, B.; Rockson, P.; Kenyanya, J.; Nzotta, C.C.
Abstract: Objectives: The Bonn call for action, with the theme: "Setting the scene for the next decade, " was declared over nine years ago to strengthen radiation protection in medicine. This study reviews key actions and activities related to radiation protection of children and adolescents consistent with the Bonn call for action in sub-Saharan Africa to highlight progress and identify existing gaps. Key findings: A lot has happened since the declaration of the Bonn call-for-action such as a follow-up conference in 2017 on achieving change in the practice of radiation protection. However, there exists a huge gap that needs to be filled in the radiation protection of children and adolescents in low and middle-income countries particularly sub-Saharan Africa, where limited resources in health compete with radiation protection demands. Some of the gaps that remain are the apparent lack of implementation of the use of referral guidelines and establishment of national and regional diagnostic reference levels for paediatric imaging among others. Conclusion: Several strides have been achieved on a global scale for the Bonn call for action, ranging from the justification of medical exposures to the current drive for radiation safety culture in medical imaging. However, several unmet needs for radiation protection for children and adolescents remain such as implementation of referral guidelines for justification and paediatric diagnostic reference levels. Implications for practice: Step up actions and close collaboration is required to strengthen the practice of paediatric radiation protection in low and middle-income countries because children account for a greater proportion of the population and are vulnerable to the negative effects of radiation like possible cancer induction.